Ideal Mentor-Perception of Faculty and Students - Shamsunnisa Sadia, Rehan Ahmed Khan, Raazia Rauf, Asma Shaheen, Fareesa Waqar (Journal of Islamic International Medical College, 2021)
Background: Mentoring implies a 2-way relationship between the mentor and the mentee. A successful partnership can lead to the professional development of both individuals. Although the significance of mentoring programs has beenrealized in the developing countries, its role in the holistic development of our students is still not given its due importance.There are important questions to be answered; who should be a mentor? What are the qualities students look for in an ideal mentor? These gaps in research are especially significant in our part of the world, where robust mentoring systems have yet to be established. Objective: To compare the perceptions of our faculty and students regarding the qualities of an ideal mentor as measured by Ideal Mentor Scale (IMS). Study Design: Cross-sectional study. Place and Duration of Study: At Pakistan Railway Hospital, Rawalpindi, Pakistan during July 2013 to August 2013. Materials and Methods: Seventy participants (faculty members:26, students:44) participated in the survey using the “Ideal Mentor Scale” (Gail Rose, The University of Iowa, 1999) to identify the relative importance of integrity, guidance and relationship in a potential mentor using a 5-point rating scale. Results: Integrity (average sum of means: 58) was considered to be the most important attribute of an ideal mentor followed by guidance (40) and relationship (35) by all the participants (undergraduate: postgraduate: faculty member). However, in the scale of relationship the undergraduate students gave higher score than the postgraduates and faculty members (3.8: 3.5: 3.3). Conclusion: Successful mentoring most importantly requires a mentor who can be emulated as a role model due to his/her principled behavior and integrity.